Religion in Public Health-Care Institutions: U.S. and U.K. Perspectives - Idler, Ellen L. (Journal for the scientific study of religion, 2017)
In this article, we consider the role that religion plays in the health-care institutions of the United States and the United Kingdom. Religion has played a significant role in the development of health-care institutions in both countries and continues to be present in them in important ways. To capture the range of involvement of religious groups in various sectors of the health-care institution, we propose a continuum for their relationship, from completely merged identities at one end (faith-saturated) to entirely separate ones at the other (faith-secular partnerships). Versions of this scheme have appeared in both U.S. and U.K. reports that describe the faith component of faith-based organizations that work in global contexts. We apply this framework to identify specific U.S. and U.K. exemplars, finding that examples of all types exist in both societies, despite the more secular nature of the United Kingdom. Accurately characterizing the relationship between religion and public health-care institutions can inform future policy and research.